Automatic design of slanted wall anechoic chamber using 3D deterministic ray tube method. Issue 11 (23rd July 2020) - Song, W. Y.; Kim, Y. D.; Lee, J. H.; Kim, H. J.; Yu, J. W.
Abstract : In order to make an anechoic chamber operate similarly to ideal OATS, various design methods of the anechoic chamber have been studied. Without changing of RAM and major structural design of the rectangle anechoic chamber, we propose a method of automatically designing the shape of a slanted wall anechoic chamber by applying the PSO to 3D deterministic ray tube method. The 3D Deterministic Ray Tube method enables efficient and fast calculation of the electric field in any slanted wall anechoic chamber. The optimized slanted wall anechoic chamber has very good performance for NSA, sVSWR compared to the general rectangle chamber.